BRAF mutations in thyroid cancer. Issue 1 (11th January 2022) - Scheffel, Rafael Selbach; Dora, Jose Miguel; Maia, Ana Luiza
Abstract : Purpose of review: Activating mutations in the mitogen-activated protein kinase (MAPK) pathway play an important role in papillary (PTC) and anaplastic (ATC) thyroid cancer. The aim of this review is to discuss the impact of BRAF mutations on clinical features and treatment of patients with thyroid cancer. Recent findings: Despite the unfavorable course associated with PTCs harboring BRAF V600E mutation, its prognostic role remains debated. BRAF V600E-driven tumors exhibit high Extracellular signal-regulated kinase phosphorylation, leading to unregulated cell proliferation and inhibition of the required genes for radioiodine responsiveness in thyroid cancer. The mechanism associated with the variable BRAF -mutant tumor aggressiveness remains unclear and other pathways are likely to co-operate to promote cancer progression. Overexpression of the Notch signaling and loss of individual switch/ sucrose non-fermentable chromatin-remodeling complexes subunits might be involved. The combination of the BRAF inhibitor dabrafenib and the mitogen-activated protein kinase kinase inhibitor trametinib has shown remarkable results in clinical trials of patients with BRAF -mutated ATCs. Summary: The impact of BRAF mutations on the clinical outcomes of PTC remains debatable. In ATCs, in turn, BRAF mutations identify patients eligible for targeted therapy, which is now considered in two settings: as neoadjuvant for unresectable tumors and as a treatment for metastatic or unresectable disease.